Técnica de comunicação por luz visível em um conversor rebaixador para sistemas de iluminação a LED - Loose, Felipe (2018)
This work presents the complete formulation of a synchronous buck converter operating as a Light Emitting Diode (LED) driver for Visible Light Communication (VLC). It also presentes a state of the art review on VLC technology. VLC consists on the use of LEDs as transmitters of digital information by modulating their light throughout an optical wireless channel. The converter is able to synthetize a binary phase shift keying (BPSK) modulation at the LED’s current while operating as power source for both communication and illumination functions. The modulation is given by the phase change of the converter’s inherent ripple waveform, which transmits data without requiring any other extra power components. Given this reason, this application is advantageous to be in VLC networks composed by sensor networks and many other Internet of Things environments of low implementation cost. Moreover, the complete mathematical modeling of the converter as part of a communication system is given. The Bit Error Rate is evaluated by means of simulations and analytical results. Finally, experimental results in a 22,6 W LED load validate the propsoed theory and show the impacts imposed by the communication functin on the system’s efficacy.